Lithium-sulfur battery and method for manufacturing lithium-sulfur battery
By designing a multi-layer structure containing sulfide solid electrolyte and polymer electrolyte in a lithium sulfur battery, the short circuit problem caused by the expansion and contraction of the positive electrode layer during charging and discharging is solved, and the effect of high battery capacity is achieved.
Patent Information
- Application Number
- CN202410980018.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-19
- Filing Date
- 2024-07-22
- Publication Date
- 2025-04-22
AI Technical Summary
The solid electrolyte layer in the lithium sulfur battery cannot follow the expansion and contraction of the positive electrode layer during charging and discharging, resulting in a possible short circuit. At the same time, if a solid electrolyte layer following expansion and contraction is used, the battery capacity will be significantly reduced.
By using a first solid electrolyte layer containing a sulfide solid electrolyte and a second solid electrolyte layer containing a polymer electrolyte and/or a gel electrolyte, short circuits can be suppressed and high battery capacity can be maintained.
It effectively suppresses short circuits that may occur during charging and discharging, and can obtain high battery capacity, achieving both.
Smart Images

Figure CN119864496A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lithium-sulfur battery and a method for manufacturing the lithium-sulfur battery. Background Art
[0002] Lithium-sulfur batteries are batteries that use sulfur as a positive electrode active material. Since sulfur has a high theoretical capacity, it has attracted attention as a next-generation battery. In liquid-type lithium-sulfur batteries, capacity degradation occurs due to the dissolution of lithium polysulfide into the electrolyte. Therefore, solid-state battery-type lithium-sulfur batteries including a solid electrolyte layer have been developed. The following solid-state battery-type lithium-sulfur batteries are known.
[0003] For example, Japanese Patent Publication No. 2023-009988 discloses the following all-solid-state battery. The all-solid-state battery has a first electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a second electrode layer in sequence. The first solid electrolyte layer has a first surface. The second solid electrolyte layer has a second surface in contact with the first surface. The maximum height Rz1 of the first surface and the maximum height Rz2 of the second surface satisfy a specific relationship. According to the all-solid-state battery of Japanese Patent Publication No. 2023-009988, even if a crack occurs in one of the first solid electrolyte layer and the second solid electrolyte layer, it is easy to suppress the crack from propagating to the other layer, and it is easy to ensure excellent short circuit resistance. Summary of the invention
[0004] The solid electrolyte layer containing a sulfide solid electrolyte has excellent properties as a solid electrolyte layer, but cannot follow the expansion and contraction of the sulfur-containing positive electrode layer accompanying charging and discharging, and cracks are generated in the solid electrolyte layer, which may cause a short circuit. In addition, when a solid electrolyte layer that follows the expansion and contraction is used to prevent short circuits, the capacity may be significantly reduced. Therefore, the solid electrolyte layer in the lithium-sulfur battery needs to be further improved.
[0005] Therefore, an object of the present disclosure is to provide a lithium-sulfur battery that can suppress short circuits associated with charge and discharge and can obtain a high battery capacity.
[0006] The present disclosure adopts the following means to achieve the above-mentioned objectives.
[0007] Solution 1
[0008] A lithium-sulfur battery having, in sequence, a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer, wherein the first solid electrolyte layer comprises a sulfide solid electrolyte, and the second solid electrolyte layer comprises a polymer electrolyte and / or a gel electrolyte.
[0009] Solution 2
[0010] The lithium-sulfur battery according to embodiment 1, wherein the negative electrode layer has a negative electrode collector layer, and lithium ions moved from the positive electrode layer during charge are deposited as metallic lithium between the second solid electrolyte layer and the negative electrode collector layer.
[0011] Solution 3
[0012] The lithium-sulfur battery according to embodiment 1 or 2, wherein the second solid electrolyte layer comprises a polymer electrolyte.
[0013] Solution 4
[0014] The lithium-sulfur battery according to any one of Schemes 1 to 3, wherein the polymer electrolyte comprises polyethylene oxide.
[0015] Solution 5
[0016] The method for manufacturing a lithium-sulfur battery according to any one of schemes 1 to 4 comprises the following steps:
[0017] The pre-positive electrode layer, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer are sequentially stacked to form a pre-stacked body, wherein the pre-positive electrode layer contains sulfur and a sulfide containing phosphorus and sulfur;
[0018] The preliminary stack is subjected to a discharge operation, so that part of the sulfur in the preliminary positive electrode layer and the sulfide containing phosphorus and sulfur react with lithium to generate a sulfide solid electrolyte, thereby forming the positive electrode layer.
[0019] The lithium-sulfur battery of the present disclosure can suppress short circuits associated with charge and discharge and can obtain a high battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will be described below with reference to the accompanying drawings, wherein like reference numerals represent like elements, and wherein:
[0021] Figure 1 It is a schematic diagram for explaining the lithium-sulfur battery of the present disclosure. DETAILED DESCRIPTION
[0022] The following is a detailed description of the embodiments of the present disclosure. In addition, the present disclosure is not limited to the following embodiments, and can be implemented in various ways within the scope of the main purpose of the present disclosure. In addition, the same reference numerals are used to mark the same elements in the description of the drawings, and repeated descriptions are omitted.
[0023] The lithium-sulfur battery of the present disclosure is a solid battery having a solid electrolyte layer as an electrolyte layer. In the present disclosure, a "solid battery" refers to a battery using at least a solid electrolyte as an electrolyte, and thus a solid battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte.
[0024] In the present disclosure, "composite material" refers to a composition that can directly constitute a positive electrode (negative electrode) layer or a solid electrolyte layer, or that can constitute a positive electrode (negative electrode) layer or a solid electrolyte layer by further containing other components. In addition, in the present disclosure, "composite material slurry" refers to a slurry that contains a dispersion medium in addition to the "composite material" and can be applied and dried to form a positive electrode (negative electrode) layer or a solid electrolyte layer.
[0025] Lithium-sulfur battery
[0026] The lithium-sulfur battery disclosed herein has a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer in sequence, the first solid electrolyte layer comprising a sulfide solid electrolyte, and the second solid electrolyte layer comprising a polymer electrolyte and / or a gel electrolyte.
[0027] According to the lithium-sulfur battery of the present disclosure, short circuits associated with charge and discharge can be suppressed, and high battery capacity can be obtained.
[0028] Specifically, for example Figure 1 As shown, the lithium-sulfur battery of the present disclosure comprises: a positive electrode layer 110, a first solid electrolyte layer 210 including a sulfide solid electrolyte, a second solid electrolyte layer 220 including a polymer electrolyte and / or a gel electrolyte, and a negative electrode layer 310. When charging and discharging are performed, the positive electrode layer 110 including sulfur as a positive electrode active material expands and contracts.
[0029] The lithium-sulfur battery disclosed herein has a second solid electrolyte layer containing a polymer electrolyte and / or a gel electrolyte. It is presumed that the second solid electrolyte layer is relatively soft because it contains a polymer electrolyte layer and / or a gel electrolyte layer, and can follow the expansion and contraction of the positive electrode layer containing sulfur accompanying charge and discharge, thereby being able to suppress short circuits.
[0030] In addition, the lithium-sulfur battery of the present disclosure has a first solid electrolyte layer containing a sulfide solid electrolyte between the positive electrode layer and the second solid electrolyte layer containing a polymer electrolyte and / or a gel electrolyte. It is speculated that since the first solid electrolyte layer is a sulfide solid electrolyte, it is possible to reduce the obstacle (barrier) for lithium to be inserted into the positive electrode layer, thereby enabling the lithium-sulfur battery to obtain a high battery capacity.
[0031] The composition of lithium-sulfur batteries
[0032] The lithium-sulfur battery disclosed herein has a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer in this order.
[0033] Positive electrode layer
[0034] The positive electrode layer contains at least a positive electrode active material. When the battery is charged, lithium ions move from the positive electrode active material to the negative electrode layer via the first solid electrolyte layer and the second solid electrolyte layer. In addition, when the battery is discharged, the lithium in the negative electrode layer is ionized and returns to the positive electrode active material. The positive electrode layer has a positive electrode active material layer and an optional positive electrode collector layer.
[0035] Positive electrode collector layer
[0036] The material used for the positive electrode collector layer is not particularly limited, and a material generally used as a positive electrode collector of a lithium-sulfur battery can be appropriately used. Examples of materials used for the positive electrode collector layer include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, etc., but are not limited thereto. In addition, the positive electrode collector layer may have some coating on its surface in order to adjust the resistance, etc. In addition, the positive electrode collector layer may be a product obtained by plating or vapor-depositing the above metal on a metal foil or a substrate.
[0037] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0038] The thickness of the positive electrode current collector layer is not particularly limited, and may be 0.1 μm or more, or 1 μm or more, and may be 1 mm or less, or 100 μm or less.
[0039] Positive electrode active material layer
[0040] The positive electrode active material layer contains at least sulfur as a positive electrode active material, and optionally may contain a conductive aid, a binder, a solid electrolyte, etc. In addition, the positive electrode active material layer may contain various additives. The content of each of the positive electrode active material, conductive aid, binder, solid electrolyte, etc. in the positive electrode active material layer can be appropriately determined according to the target battery performance. For example, when the entirety of the positive electrode active material layer (the entirety of the solid component) is set to 100% by mass, the content of the positive electrode active material may be more than 40% by mass, more than 50% by mass, more than 60% by mass, and may be less than 100% by mass, or less than 90% by mass.
[0041] Positive active material
[0042] As described above, as the positive electrode active material, at least sulfur is used. Sulfur may be simple sulfur or a sulfur compound as long as it can function as a positive electrode active material.
[0043] In addition, the positive electrode active material layer may contain positive electrode active materials other than elemental sulfur and sulfur compounds. Examples of positive electrode active materials other than elemental sulfur and sulfur compounds include various lithium-containing compounds. Examples of lithium-containing compounds include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), nickel-cobalt-manganese oxide (NCM), LiCoO2, and lithium tantalum (T). 1 / 3 Ni 1 / 3Mn 1 / 3 O2, nickel-cobalt-aluminum oxide (NCA: LiNi x Co y Al z O2). In addition, the lithium-containing compound may be Li 1+x Mn 2-x-y M y O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn) is a heterogeneous element substituted Li-Mn spinel, etc. However, the lithium-containing compound is not limited to these.
[0044] There is no particular limitation on the ratio of elemental sulfur and sulfur compounds contained in the positive electrode active material layer, and may be 50% to 100% by mass, 60% to 100% by mass, 70% to 100% by mass, 80% to 100% by mass, or 90% to 100% by mass relative to the positive electrode active material layer.
[0045] The shape of the positive electrode active material is not particularly limited as long as it is a general shape of the positive electrode active material for lithium-sulfur batteries. The positive electrode active material may be, for example, in the form of particles. The positive electrode active material may be solid or hollow, may have gaps, or may be porous. The positive electrode active material may be a primary particle or a secondary particle formed by agglomeration (aggregation) of a plurality of primary particles. The average particle size D of the positive electrode active material is 50 For example, the average particle size D may be 1 nm or more, 5 nm or more, or 10 nm or more, and may be 500 μm or less, 100 μm or less, 50 μm or less, or 30 μm or less. 50 It is a particle diameter (median diameter) at a cumulative value of 50% in a volume-based particle size distribution determined by a laser diffraction / scattering method.
[0046] Conductive additives
[0047] There is no particular limitation on the conductive aid. The conductive aid may be, for example, vapor grown carbon fiber (VGCF), acetylene black (AB), Ketjen black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto. The conductive aid may be, for example, in the form of particles or fibers, and its size is not particularly limited. There is no particular limitation on the conductive aid, and only one type may be used alone, or two or more types may be used in combination.
[0048] Adhesives
[0049] As the adhesive, there is no particular limitation. The adhesive may be, for example, polyvinylidene fluoride (PVdF), butadiene rubber (BR), polytetrafluoroethylene (PTFE), styrene butadiene rubber (SBR) and the like, but is not limited thereto. The adhesive is not particularly limited, and only one may be used alone, or two or more may be used in combination.
[0050] Solid electrolyte
[0051] The material of the solid electrolyte is not particularly limited, and may be a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte.
[0052] For the sulfide solid electrolyte, reference may be made to the description of "<First solid electrolyte layer>" described later. For the polymer electrolyte, reference may be made to the description of "<Second solid electrolyte layer>" described later.
[0053] Examples of oxide solid electrolytes include Li7La3Zr2O 12 , Li 7-x Ln3Z 1-x Nb x O 12 , Li 7- 3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3、Li 1+x Al x Ti 2-x (PO4)3、Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4- x N x (LiPON), etc. However, the oxide solid electrolyte is not limited to these.
[0054] The oxide solid electrolyte may be glass or crystallized glass (glass ceramic).
[0055] The shape of the positive electrode active material layer is not particularly limited, and for example, it can be a sheet-shaped positive electrode active material layer with a substantially flat surface. The thickness of the positive electrode active material layer is not particularly limited, and for example, it can be 0.1 μm or more, 1 μm or more, or 10 μm or more, and can be 2 mm or less, 1 mm or less, or 500 μm or less.
[0056] The positive electrode layer can be manufactured by a known method. For example, the positive electrode active material layer can be easily formed by forming the positive electrode composite material containing the above-mentioned various components in a dry or wet manner. The positive electrode active material layer can be formed together with the positive electrode collector layer, or it can be formed separately from the positive electrode collector layer (independently formed).
[0057] First solid electrolyte layer
[0058] In the lithium-sulfur battery of the present disclosure, the first solid electrolyte layer includes a sulfide solid electrolyte.
[0059] The first solid electrolyte layer contains a sulfide solid electrolyte, and may further optionally contain a binder and the like.
[0060] Sulfide solid electrolyte
[0061] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5 (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2 (Li 13 GeP3S 16 , Li 10 GeP2S 12 etc.), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x PS 6-x Cl x etc. or a combination of these. However, the sulfide solid electrolyte is not limited to these.
[0062] The sulfide solid electrolyte may be glass or crystallized glass (glass ceramic).
[0063] Regarding the binder, reference can be made to the description in the above-mentioned “<Positive Electrode Active Material Layer>”.
[0064] The thickness of the first solid electrolyte layer is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, or 10 μm or more, and may be 2 mm or less, 1 mm or less, or 500 μm or less.
[0065] The first solid electrolyte layer can be easily formed by, for example, molding an electrolyte composite material including the above-mentioned sulfide solid electrolyte and a binder etc. in a dry or wet manner.
[0066] Second solid electrolyte layer
[0067] In the lithium-sulfur battery of the present disclosure, the second solid electrolyte layer comprises a polymer electrolyte and / or a gel electrolyte. The second solid electrolyte layer is not particularly limited, but preferably comprises a polymer electrolyte.
[0068] Polymer Electrolyte
[0069] The polymer electrolyte refers to an electrolyte having a solvent content of 5% by mass or less. The solvent content may be 3% by mass or less, or 1% by mass or less.
[0070] The polymer electrolyte comprises at least a polymer component. As the polymer component, for example, polyether polymers, polyester polymers, polyamine polymers, polysulfide ether polymers, etc. can be listed, but it is not limited to these. From the viewpoint of mechanical properties such as ionic conductivity and Young's modulus, polyether polymers are preferred.
[0071] The polyether polymer is not particularly limited, but polyethylene oxide is preferred. That is, the polymer electrolyte is not particularly limited, but preferably contains polyethylene oxide.
[0072] The polyether polymer is not particularly limited, but preferably has a polyether structure in the main chain of the repeating unit. Examples of the polyether structure include, but are not limited to, polyethylene oxide (PEO) structure and polypropylene oxide (PPO) structure.
[0073] The polyether polymer is not particularly limited, and preferably has a PEO structure as the main repeating unit. The proportion of the PEO structure can be, for example, 50-100 mol%, 60-100 mol%, 70-100 mol%, 80-100 mol%, or 90-100 mol%. In addition, the polyether polymer can be, for example, a homopolymer or copolymer of an epoxy compound (e.g., ethylene oxide, propylene oxide).
[0074] The polymer component may have the following ion conductive units. Examples of the ion conductive unit include polyethylene oxide, polypropylene oxide, polymethacrylate, polyacrylate, polydimethylsiloxane, polyacrylic acid, polymethacrylic acid, polyethylene vinyl acetate, polyimide, polyamine, polyamide, polyalkyl carbonate, polynitrile, polyphosphazene, polyolefin, and polydiene.
[0075] The weight average molecular weight of the polymer component is not particularly limited, but is, for example, 1,000,000 to 10,000,000 or less. The weight average molecular weight can be determined by gel permeation chromatography (GPC).
[0076] The polymer electrolyte may be a single polymer component or a combination of two or more polymer components. The polymer electrolyte may be a cross-linked polymer electrolyte in which the polymer component is cross-linked or a non-cross-linked polymer electrolyte in which the polymer component is not cross-linked.
[0077] The polymer electrolyte may contain a supporting salt (lithium salt). The supporting salt (lithium salt) is not particularly limited, and inorganic lithium salts, organic lithium salts, etc. may be cited. As inorganic lithium salts, for example, LiPF6, LiBF4, LiClO4, LiAsF6, etc. may be cited, but are not limited to these. As organic lithium salts, for example, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, LiC(CF3SO2)3, etc. may be cited, but are not limited to these. For example, in the case where the polymer electrolyte has an EO unit (C2H5O unit), the EO unit is not particularly limited relative to 1 mol part of the supporting salt, and may be 5 mol parts or more, 10 mol parts or more, or 15 mol parts or more, and may be 40 mol parts or less, or 30 mol parts or less.
[0078] Gel Electrolyte
[0079] The gel electrolyte contains an electrolyte solution in addition to the polymer electrolyte.
[0080] Electrolyte
[0081] The electrolyte solution is not particularly limited, but preferably contains a supporting salt and a solvent. For the supporting salt, reference can be made to the description of the above "(Polymer Electrolyte)".
[0082] As the solvent used for the electrolyte, there is no particular limitation, and cyclic carbonates, chain carbonates, etc. can be listed. As cyclic carbonates, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be listed, but they are not limited to these. As chain carbonates, for example, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), etc. can be listed, but they are not limited to these. In addition, as solvents, for example, acetates such as methyl acetate and ethyl acetate can be listed; ethers such as 2-methyltetrahydrofuran, etc., but they are not limited to these. Furthermore, as solvents, for example, γ-butyrolactone, cyclopentane sulfone, N-methylpyrrolidone (NMP), 1,3-dimethyl-2-imidazolidinone (DMI), etc. can be listed, but they are not limited to these. In addition, the solvent can be water.
[0083] The thickness of the second solid electrolyte layer is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, or 10 μm or more, and may be 2 mm or less, 1 mm or less, or 500 μm or less.
[0084] The second solid electrolyte layer can be easily formed, for example, by dissolving the above-mentioned polymer electrolyte and / or gel electrolyte, and supporting salt, etc. in a solvent, and molding a second solid electrolyte layer precursor solution containing the above-mentioned various components.
[0085] Negative electrode layer
[0086] The negative electrode layer may include only the negative electrode collector layer, or may include the negative electrode active material layer and the negative electrode collector layer. When the battery is charged, the lithium ions moved from the positive electrode accept electrons and can be precipitated as metallic lithium between the second solid electrolyte layer and the negative electrode collector layer. In addition, when the battery is charged, the lithium ions moved from the positive electrode accept electrons and can be retained in the negative electrode active material of the negative electrode active material layer. When the battery is discharged, the lithium in the negative electrode layer is ionized and returns to the positive electrode layer.
[0087] Negative electrode active material layer
[0088] The negative electrode active material layer contains at least a negative electrode active material, and optionally, may contain a conductive aid, a binder, a solid electrolyte, etc. In addition, the negative electrode active material layer may contain various additives. The respective contents of the negative electrode active material, conductive aid, binder, solid electrolyte, etc. in the negative electrode active material layer can be appropriately determined according to the target battery performance. For example, when the entirety of the negative electrode active material layer (the entirety of the solid component) is set to 100% by mass, the content of the negative electrode active material may be 40% by mass or more, 50% by mass or more, or 60% by mass or more, and may be 100% by mass or less, or 90% by mass or less.
[0089] Negative active material
[0090] As the negative electrode active material, various materials having a potential (charge and discharge potential) for absorbing and releasing lithium ions that is lower than that of the positive electrode active material disclosed above can be used. There is no particular limitation on the material of the negative electrode active material, and it can be metallic lithium or a material that can absorb and release metal ions such as lithium ions. As materials that can absorb and release metal ions such as lithium ions, for example, alloy-based negative electrode active materials or carbon materials can be listed, but they are not limited to these. Among them, there is no particular limitation on the material of the negative electrode active material, and metallic lithium is preferred.
[0091] There is no particular limitation on alloy-based negative electrode active materials, and examples thereof include Si alloy-based negative electrode active materials or Sn alloy-based negative electrode active materials. Si alloy-based negative electrode active materials include silicon, silicon oxide, silicon carbide, silicon nitride, or their solid solutions. In addition, Si alloy-based negative electrode active materials may contain metal elements other than silicon, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, etc. Sn alloy-based negative electrode active materials include tin, tin oxide, tin nitride, or their solid solutions. In addition, Sn alloy-based negative electrode active materials may contain metal elements other than tin, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Ti, Si, etc.
[0092] The carbon material is not particularly limited, and examples thereof include hard carbon, soft carbon, and graphite.
[0093] The shape of the negative electrode active material is not particularly limited, and any general shape of the negative electrode active material of the lithium-sulfur battery may be used. The negative electrode active material may be in the form of a sheet or a particle. The negative electrode active material may be accompanied by lithium precipitation during charging, or may be accompanied by lithium dissolution during discharging. In this case, the negative electrode active material layer may be a layer composed of metallic lithium or a lithium alloy (e.g., metallic lithium foil, lithium alloy foil).
[0094] The conductive aid, binder, and solid electrolyte that may be contained in the negative electrode active material layer may refer to the description of the above-mentioned “<Positive electrode active material layer>”.
[0095] The shape of the negative electrode active material layer is not particularly limited, and may be, for example, a substantially flat sheet-shaped negative electrode active material layer. The thickness of the negative electrode active material layer is not particularly limited, and may be, for example, 0.1 μm or more, 1 μm or more, or 10 μm or more, and may be 2 mm or less, 1 mm or less, or 500 μm or less.
[0096] Negative electrode collector
[0097] The material used in the negative electrode collector layer is not particularly limited, and a general material used as a negative electrode collector of a lithium-sulfur battery can be appropriately used. As the material used in the negative electrode collector layer, Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, stainless steel, or carbon sheet can be listed, but it is not limited to these. In particular, from the viewpoint of ensuring reduction resistance and the viewpoint of difficulty in alloying with lithium, the material used for the negative electrode collector layer may include at least one metal selected from Cu, Ni and stainless steel, and may also be composed of a carbon sheet. In order to adjust the resistance, etc., the negative electrode collector layer may have some coating on its surface.
[0098] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.
[0099] The thickness of the negative electrode current collector layer is not particularly limited, and may be 0.1 μm or more, or 1 μm or more, and may be 1 mm or less, or 100 μm or less.
[0100] The negative electrode layer can be manufactured by applying a known method. For example, the negative electrode active material layer can be easily formed by forming the negative electrode composite material containing the above-mentioned various components in a dry or wet manner. The negative electrode active material layer can be formed together with the negative electrode collector layer, or can be formed separately from the negative electrode collector layer (independently formed).
[0101] Figure 1 This is a schematic diagram showing one embodiment of the lithium-sulfur battery of the present disclosure, but the present invention is not limited to this embodiment.
[0102] Figure 1 The lithium-sulfur battery 100 has a structure in which a positive electrode layer 110, a first solid electrolyte layer 210, a second solid electrolyte layer 220, and a negative electrode layer 310 are stacked. The positive electrode layer 110 contains sulfur, and the first solid electrolyte layer 210 contains a sulfide solid electrolyte. In addition, the second solid electrolyte layer 220 contains a polymer electrolyte and / or a gel electrolyte. The second solid electrolyte layer contains a polymer electrolyte and / or a gel electrolyte, so it is relatively soft and can follow the expansion and contraction of the positive electrode layer containing sulfur accompanying charging and discharging, thereby suppressing short circuits. In addition, the first solid electrolyte contains a sulfide solid electrolyte, so that the barrier to the insertion of lithium into the positive electrode layer can be reduced, thereby enabling the lithium-sulfur battery to obtain a high battery capacity.
[0103] Method for manufacturing lithium-sulfur battery
[0104] The lithium-sulfur battery disclosed herein can be produced by a production method including the following steps.
[0105] The pre-positive electrode layer, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer are sequentially stacked to form a pre-stacked body, wherein the pre-positive electrode layer contains sulfur and a sulfide containing phosphorus and sulfur;
[0106] The preliminary stack is subjected to a discharge operation, so that part of the sulfur in the preliminary positive electrode layer and the sulfide containing phosphorus and sulfur react with lithium to generate a sulfide solid electrolyte, thereby forming the positive electrode layer.
[0107] Formation of pre-laminated body
[0108] The method may include sequentially stacking a pre-positive electrode layer including sulfur and a sulfide containing phosphorus and sulfur, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer to form a pre-stacked body.
[0109] Pre-positive electrode layer
[0110] The pre-positive electrode layer contains sulfur and sulfide containing phosphorus and sulfur.
[0111] Sulfides containing phosphorus and sulfur
[0112] The sulfide contains at least phosphorus and sulfur. The pre-positive electrode layer may contain only a sulfide containing phosphorus and sulfur, or may further contain a sulfide containing other elements (such as Ge, Sn, Si, B or Al) and sulfur. In the latter case, the pre-positive electrode layer preferably contains a sulfide containing phosphorus and sulfur as the main body of the sulfide.
[0113] The sulfide preferably contains the ortho structure of the phosphorus element. As the ortho structure of the phosphorus element, for example, a PS4 structure can be cited, but it is not limited to this case. In addition, the sulfide may contain the ortho structure of the M element (M is, for example, Ge, Sn, Si, B or Al, etc.). As the ortho structure of the M element, for example, a GeS4 structure, a SnS4 structure, a SiS4 structure, a BS3 structure, an AlS3 structure, etc. can be cited, but it is not limited to these cases. On the other hand, the sulfide may contain the sulfide of the phosphorus element (for example, P2S5). In addition, the sulfide may have a sulfide of the M element (M x S y ). Here, x and y are integers that impart electrical neutrality to S according to the type of M. As a sulfide (M x S y ), for example, GeS2, SnS2, SiS2, B2S3, Al2S3, etc. can be listed, but it is not limited to these.
[0114] The sulfur element in the sulfide may have a chemical bond (SS bond) with the sulfur element in the elemental sulfur or sulfur compound as the positive electrode active material. In particular, it is preferred that the sulfur element in the original structure has a chemical bond (SS bond) with the sulfur element in the elemental sulfur as the positive electrode active material.
[0115] In the pre-positive electrode layer, the molar ratio of phosphorus to sulfur (phosphorus / sulfur) is not particularly limited, and may be greater than 0.03, greater than 0.06, greater than 0.09, or greater than 0.12, and may be less than 0.50, less than 0.30, or less than 0.27. Furthermore, the denominator of the molar ratio (phosphorus / sulfur) means the amount of all sulfur contained in the pre-positive electrode layer. In the present disclosure, both the positive electrode active material and the sulfide contain sulfur, so it is the total amount of sulfur in the two.
[0116] Lithium in the pre-electrode layer
[0117] The pre-positive electrode layer may be substantially free of lithium. The term “substantially free of lithium” means that the ratio of lithium to all elements contained in the pre-positive electrode layer is 20 mol% or less. The ratio of lithium may be 15 mol% or less, 10 mol% or less, 5 mol% or less, or 1 mol% or less.
[0118] Positive electrode composites containing solid electrolytes containing lithium elements are known. For example, when using a solid electrolyte using Li2S as a raw material, the battery using such a positive electrode composite for the positive electrode layer tends to have a reduced capacity due to the low water resistance of Li2S. However, the pre-positive electrode layer in the method for manufacturing a lithium-sulfur battery disclosed in the present invention can suppress the reduction in the capacity of the lithium-sulfur battery without substantially containing lithium elements (such as Li2S).
[0119] For the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer, reference can be made to the description in the above-mentioned “<Configuration of lithium-sulfur battery>”.
[0120] There is no particular limitation on the method for forming the pre-laminated body. Specifically, for example, the first solid electrolyte layer is stacked on the pre-positive electrode layer and pressed to obtain a laminate of the pre-positive electrode layer and the first solid electrolyte layer. Next, the second solid electrolyte layer and the negative electrode layer are sequentially stacked on the first solid electrolyte layer of the laminate, the positive and negative terminals are connected, and the laminate is sealed with a laminate film, thereby obtaining a laminate of the pre-laminated body.
[0121] Formation of positive electrode layer
[0122] The method for manufacturing a lithium-sulfur battery disclosed herein can discharge the pre-stacked body to react a portion of sulfur in the pre-positive electrode layer and a sulfide containing phosphorus and sulfur with lithium to generate a sulfide solid electrolyte, thereby forming the positive electrode layer.
[0123] Discharge operation
[0124] The discharge operation is not particularly limited and can be performed in a temperature environment of 60° C. or higher. The temperature environment may be 80° C. or higher, or 100° C. or higher, and 200° C. or lower. The discharge operation is usually performed on the pre-laminated body in a state where the surface temperature of the pre-laminated body is the same as the ambient temperature.
[0125] The discharge rate in the discharge operation is not particularly limited, and may be, for example, 0.01C or more, 0.05C or more, or 0.10C or more, and may be 0.50C or less, or 0.33C or less.
[0126] During the discharge operation, the pre-electrode stack may be constrained. The pre-electrode stack may be constrained at, for example, 1 MPa, but is not limited thereto.
[0127] Sulfide preferably becomes an ion conduction path during charge and discharge. During discharge, lithium ions are conducted from the negative electrode layer to the pre-positive electrode layer via the second solid electrolyte and the first solid electrolyte, and the lithium ions reaching the pre-positive electrode layer react with the positive electrode active material. In the case where there is no sulfide in the pre-positive electrode layer, the ion conductivity of the discharge product of sulfur (such as Li2S) as the positive electrode active material is low, so the ion conduction path in the pre-positive electrode layer is insufficient, and the discharge reaction is difficult to proceed. On the other hand, in the case where there is a sulfide in the pre-positive electrode layer, even if the ion conductivity of the discharge product of sulfur (such as Li2S) as the positive electrode active material is low, the ion conduction path in the pre-positive electrode layer can be ensured by the sulfide, so the discharge reaction is easy to proceed.
[0128] The present disclosure will be described in more detail with reference to the following examples, but the scope of the present disclosure is not limited to these examples.
[0129] Example 1
[0130] Preparation of pre-cathode layer
[0131] Sulfur (S) (42 parts by mass) as a positive electrode active material, phosphorus pentasulfide (P2S5) (23 parts by mass) as a sulfide containing phosphorus and sulfur, and vapor grown carbon fiber (VGCF) (35 parts by mass) as a conductive aid are mixed using a ball mill. The obtained mixed powder is put into a polypropylene (PP) container, and a 5% by mass solution of a styrene-based binder and mesitylene as a binder are added, and dispersed for 30 seconds using an ultrasonic disperser (UH-50 manufactured by SMT Co., Ltd.). Next, the dispersed mixture is vibrated for 30 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.) to prepare a pre-positive electrode composite slurry. The obtained pre-positive electrode composite slurry is modulated and coated on an aluminum (Al) foil as a positive electrode collector using a coater using a doctor blade method so that the mass per unit area becomes 7.6 mg / cm2 Then, the preliminary positive electrode material slurry was naturally dried and dried on a hot plate heated to 100° C. for 30 minutes to obtain a preliminary positive electrode layer formed on the Al foil.
[0132] Fabrication of sulfide solid electrolyte layer
[0133] Li2S-P2S5 glass ceramics containing lithium iodide (LiI) were mixed with a ball mill and sintered to obtain a sulfide solid electrolyte. Next, the obtained sulfide solid electrolyte was put into a PP container, a 5% by mass heptane solution of a butene rubber-based adhesive and heptane were added as an adhesive, and the mixture was dispersed for 30 seconds using an ultrasonic disperser (UH-50 manufactured by SMT Co., Ltd.). Next, the dispersed mixture was vibrated for 30 minutes using a vibrator (TTM-1 manufactured by Shibata Science Co., Ltd.) to prepare a sulfide solid electrolyte composite slurry. The sulfide solid electrolyte composite slurry was applied to a PET film using a doctor blade method using a coater, dried naturally, and dried on a hot plate heated to 100°C for 30 minutes to obtain a coating formed on the PET film. The coating surfaces of the coating formed on the PET film were overlapped with each other and pressed with 7 tons. Next, the PET film was peeled off to obtain a sulfide solid electrolyte layer.
[0134] Fabrication of polymer electrolyte layer
[0135] Polyethylene oxide (PEO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are dissolved in acetonitrile. The molar ratio (EO / Li) of the C2H5O unit (EO unit) of polyethylene oxide to the lithium (Li) element contained in LiTFSI is EO / Li=20 / 1 (molar ratio). To the solution, 10% by mass of benzoyl peroxide (BPO) as an initiator is added relative to the total amount of PEO and LiTFSI, and the solution is stirred until a uniform solution is obtained to prepare a polymer electrolyte layer precursor solution. Next, the polymer electrolyte layer precursor solution is applied on a polyethylene terephthalate (PET) film using a doctor blade method using a coater, and dried on a hot plate heated to 100°C for 30 minutes. Next, the PET film is peeled off to obtain a polymer electrolyte layer.
[0136] Preparation of pre-laminated body A1
[0137] The metal lithium as the negative electrode layer was punched out into φ13.00mm. Similarly, the polymer electrolyte layer and the sulfide solid electrolyte layer were punched out into φ14.50mm, and the pre-positive electrode layer was punched out into φ11.28mm. The sulfide solid electrolyte layer as the first solid electrolyte layer was overlapped on the pre-positive electrode layer processed into a circular shape, and then pressed at 7 tons to obtain a stack of the pre-positive electrode layer and the sulfide solid electrolyte layer. On the sulfide solid electrolyte layer of the stack, the polymer electrolyte layer as the second solid electrolyte layer and the metal lithium as the negative electrode layer were stacked in sequence, the positive and negative terminals were connected, and the stacked film was used to seal to obtain the pre-stack A1.
[0138] Fabrication and electrochemical evaluation of lithium-sulfur battery B1
[0139] The pre-laminated body A1 was restrained with a metal plate at a pressure of 1 MPa. Next, it was placed in a thermostatic chamber at 60°C and a constant current (0.06 mA / cm2) was passed in a cutoff voltage range of 1.2-3.1 V. 2 ) test was carried out to obtain a lithium-sulfur battery B1. Then, a charge test was carried out under the same constant current condition. The discharge capacity of the lithium-sulfur battery B1 was 6.3 mAh, the charge capacity was 5.0 mAh, and no short circuit occurred.
[0140] Comparative Example 1
[0141] Preparation of pre-laminated body a1, preparation of lithium-sulfur battery b1 and electrochemical evaluation
[0142] The metallic lithium as the negative electrode layer was punched out into φ13.00mm. Similarly, the sulfide solid electrolyte layer was punched out into φ14.50mm, and the pre-positive electrode layer was punched out into φ11.28mm. The pre-positive electrode layer processed into a circle was pressed with 7 tons, and the sulfide solid electrolyte layer as the first solid electrolyte layer and the metallic lithium as the negative electrode layer were stacked thereon in sequence, the positive and negative terminals were connected, and the laminated film was used to seal the pre-laminated body a1. The pre-laminated body a1 is a laminate that does not contain a polymer electrolyte layer as the second solid electrolyte layer relative to the pre-laminated body A1. The electrochemical evaluation of the pre-laminated body a1 was carried out in the same manner as the electrochemical evaluation of the pre-laminated body A1, and a lithium-sulfur battery b1 was obtained. The discharge capacity of the lithium-sulfur battery b1 was 6.3mAh, and the charging capacity could not be obtained due to a short circuit.
[0143] Comparative Example 2
[0144] Preparation of pre-laminated body a2, preparation of lithium-sulfur battery b2 and electrochemical evaluation
[0145] The metal lithium as the negative electrode layer was punched out into φ13.00mm. Similarly, the polymer electrolyte layer was punched out into φ14.50mm, and the pre-positive electrode layer was punched out into φ11.28mm. The pre-positive electrode layer processed into a circle was pressed with 7 tons, and the polymer electrolyte layer as the second solid electrolyte layer and the metal lithium as the negative electrode layer were stacked on it in sequence, the positive and negative terminals were connected, and the laminated film was used to seal it to obtain a pre-laminated body a2. The pre-laminated body a2 is a laminated body that does not contain a sulfide solid electrolyte layer as the first solid electrolyte layer relative to the pre-laminated body A1. The electrochemical evaluation of the pre-laminated body a2 was carried out in the same way as the electrochemical evaluation of the pre-laminated body A1, and a lithium-sulfur battery b2 was obtained. The discharge capacity of the lithium-sulfur battery b2 was 1.3mAh, the charging capacity was 0.8mAh, and no short circuit occurred.
[0146] Table 1 shows the electrochemical evaluations of Example 1 and Comparative Examples 1 and 2.
[0147] Table 1
[0148]
[0149] The lithium-sulfur battery b1 operated well in the initial discharge measurement, but short-circuited in the charge measurement after the discharge measurement. The main reason for the short circuit of the lithium-sulfur battery b1 is presumed to be that the sulfide solid electrolyte layer could not follow the expansion of the sulfur-containing positive electrode layer in the discharge measurement, and cracks occurred in the layer, thereby causing lithium precipitation in the subsequent charge treatment.
[0150] Lithium-sulfur battery b2 did not suffer from short circuit, but its initial discharge capacity was significantly reduced. This is presumably because the insertion of lithium from the polymer electrolyte layer into the sulfur-containing positive electrode layer was hindered, and thus the positive electrode active material and lithium did not move sufficiently.
[0151] On the other hand, the lithium-sulfur battery B1 operated well in the initial discharge measurement, and a discharge capacity of 6.3 mAh was obtained. In the charge measurement after the discharge measurement, a charge capacity of 5.0 mAh was obtained, and no short circuit occurred. From the above, it can be seen that by arranging a sulfide solid electrolyte between the sulfur-containing positive electrode layer and the polymer electrolyte layer, short circuits associated with charge and discharge can be suppressed, and a high battery capacity can be obtained.
[0152] The preferred embodiments of the lithium-sulfur battery and the method for manufacturing the lithium-sulfur battery of the present disclosure are described above, but those skilled in the art can understand that the present disclosure can be modified without departing from the patent claims.
Claims
1. A lithium-sulfur battery, comprising a positive electrode layer, a first solid electrolyte layer, a second solid electrolyte layer, and a negative electrode layer in sequence, The first solid electrolyte layer includes a sulfide solid electrolyte, and the second solid electrolyte layer includes a polymer electrolyte and / or a gel electrolyte.
2. The lithium-sulfur battery according to claim 1, wherein The negative electrode layer has a negative electrode current collector layer, and During charging, lithium ions transferred from the positive electrode layer are deposited as metallic lithium between the second solid electrolyte layer and the negative electrode current collector layer.
3. The lithium-sulfur battery according to claim 1, wherein The second solid electrolyte layer includes a polymer electrolyte.
4. The lithium-sulfur battery according to claim 3, wherein: The polymer electrolyte includes polyethylene oxide.
5. The method for manufacturing a lithium-sulfur battery according to any one of claims 1 to 4, comprising the following steps: The pre-positive electrode layer, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode layer are sequentially stacked to form a pre-stacked body, wherein the pre-positive electrode layer contains sulfur and a sulfide containing phosphorus and sulfur; The preliminary stack is subjected to a discharge operation, so that part of the sulfur in the preliminary positive electrode layer and the sulfide containing phosphorus and sulfur react with lithium to generate a sulfide solid electrolyte, thereby forming the positive electrode layer.
Citation Information
Patent Citations
All-solid battery and manufacturing method thereof
JP2023009988A